The relationship between lower-limb asymmetry and speed-climbing time: The role of muscle thickness and neural activation - Zhang, X.; Zhu, C.; Ou, Z.; Wu, L., Li, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study investigated lower-limb asymmetry in speed climbers and its relationship with climbing time while exploring the underlying mechanisms through muscle-thickness and activation.